Trofimova E. V. Phraseological units as nomination of negative emotions in the English and Ukrainian discourses - Trofimova E. V. (Philological Treatises, 2020)
The paper deals with the study of idioms denoting negative emotional behaviour in the English and Ukrainian languages. Different models of the negative emotional behaviour have been distinguished, explicated by the idioms. The article presents the results of the semantic and structural analysis considering the universal character and differences of the negative emotions verbalization in different language systems and cultural communities.